PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PERKEBUNAN SAWIT CV SAHABAT JAYA DI PANGKALAN KERINCI RIAU - Basriani, Agustin (Komunitas Manajemen Kompetitif, 2018)
Abstract: This study aims to determine the effect of Career Development on Employee Performance on Palm Oil Plantations CV Sahabat Jaya in Pangkalan Kerinci Riau. This research uses Explonatory Research method, with quantitative approach, data collection technique is through interview, questionnaire and documentation. The sample in this study amounted to 38 people, where the entire population is used as a Sample by using the Saturated Sampling technique. The analysis technique used is descriptive technique and using simple linear regression equation and processed using SPSS program version 23. Based on the results of this study indicate that career development has a positive and significant impact on performance. This is evidenced by the value of thitung for 6,930 and Coefficient of Determination of 52%